LITERATURE REVIEW ANALYSIS PROBLEM BASED LEARNING (PBL) LEARNING MODELS IN SCIENCE LEARNING IN PRIMARY SCHOOLS - Dwi Sari; Diyah Septiana; Anisa Enjelia; Sherina Brighita Racy Ayuni (Teaching and General Education Studies, 2025)
The research is motivated by the importance of using the Problem-Based Learning model. In this context, elementary schools use a problem-based learning model for science learning. The study's findings indicate that science learning in elementary schools employs the problem-based learning paradigm, which is associated with learning outcomes. Elementary schools use the problem-based learning paradigm in science learning.